Olivine‐rich exposures at Bellicia and Arruntia craters on (4) Vesta from Dawn FC. (October 2014) - Thangjam, Guneshwar; Nathues, Andreas; Mengel, Kurt; Hoffmann, Martin; Schäfer, Michael; Reddy, Vishnu; Cloutis, Edward A.; Christensen, Ulrich; Sierks, Holger; Corre, Lucille Le; Vincent, Jean‐Baptiste; Russell, Christopher T.
Abstract We present an analysis of olivine‐rich exposures at Bellicia and Arruntia craters using Dawn Framing Camera (FC) color data. Our results confirm the existence of olivine‐rich materials at these localities as described by Ammannito et al. (2013a) using Visual Infrared Spectrometer (VIR) data. Analyzing laboratory spectra of various howardite–eucrite–diogenite meteorites, high‐Ca pyroxenes, olivines, and olivine‐orthopyroxene mixtures, we derive three FC spectral band parameters that are indicators of olivine‐rich materials. Combining the three band parameters allows us, for the first time, to reliably identify sites showing modal olivine contents >40%. The olivine‐rich exposures at Bellicia and Arruntia are mapped using higher spatial resolution FC data. The exposures are located on the slopes of outer/inner crater walls, on the floor of Arruntia, in the ejecta, as well as in nearby fresh small impact craters. The spatial extent of the exposures ranges from a few hundred meters to few kilometers. The olivine‐rich exposures are in accordance with both the magma ocean and the serial magmatism model (e.g., Righter and Drake 1997; Yamaguchi et al. 1997). However, it remains unsolved why the olivine‐rich materials are mainly concentrated in the northern hemisphere (approximately 36–42°N, 46–74°E) and are almost absent in the Rheasilvia basin.